VR: Getting the Reality Part Straight – Does Jitter and Suspension of the Human Body Increase Auditory Circular Vection? - Feuereissen, D. (Department of Computer Science in Media, 2008)
Current developments in creating the illusion of being in a virtual world (VR simulations) aim to increase detail and technical complexity to further realism and immersion for the observer. Consistent, multimedia sensor manipulation using audio, video and self motion is the key approach to increase immersion and thus, the feeling of "being there". Despite those technical efforts, achieving a high level of immersion and reducing the appearance of simulator sickness and disorientation in VR simulations still poses quite a challenge. Physical motion brings a certain amount of financial and implementational effort along (Platforms, Treadmills, etc.) and does not yield satisfactory results when taking the ratio of effort and results into account. Previous research show, that convincing self motion can be achieved using vection, the illusion of self motion (e.g., Riecke, Schulte-Pelkum, Caniard, & Blthoff, 2005a). Not having to use physical motion devices would bring us closer to our main goal of building a lean and elegant motion simulator. In pursuit of evoking convincing self motion illusion, we manipulated auditory and vibrotactile sensor channels to determine the effect of jitter and body suspension on auditory circular vection. We quantified experiences using intensity ratings, vection onset time, direction of perceived rotation and perceived rotational speed. We found, that purely auditory vection can be achieved with the setup we used. Participants were more likely to experience vection in either combination with jitter or the body suspended. Vection ratings were higher in either condition compared to pure auditory vection, where the participant's feet are on the ground and jitter is off. Furthermore, jitter in combination with a suspended body was more likely to produce auditory vection and yielded higher intensity ratings than all conditions mentioned in above. Suspending the participiant's body and adding jitter using a simple excenter motor enhances the self motion experience and thus brings us one step closer to designing a lean and elegant self motion simulator.
Keywords: Riecke; Riecke_2008; Riecke_seniorCoSupervised_thesis; Riecke_supervised_thesis; bernhard-riecke; daniel-feuereissen; multi-modal vection; seniorCoSupervisedThesis; supervisedThesis; thesis; vection